IMPROVING CHILDREN’S SPEAKING SKILLS THROUGH HAND PUPPET MEDIA FOR 4–5-YEAR-OLDS AT TK MUTIARA INSANI - Pebriyani, Ira; Yulianty S, Nadya; Purnamasari, Rika (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This classroom action research aims to improve children’s speaking skills through the use of hand puppet media for children aged 4–5 years at TK Mutiara Insani. The subjects of this study were 16 children, consisting of 8 boys and 8 girls. The research was conducted in two cycles, with each cycle including the stages of planning, implementation, observation, and reflection. Data were collected through observation, documentation, and field notes, then analysed descriptively and qualitatively by calculating the percentage of achievement of children’s speaking skill indicators. The results showed that children’s speaking skills improved after the implementation of hand puppet media. In the initial condition, most children were still reluctant to express their opinions and had limited vocabulary. After the first cycle, their speaking skills began to improve, as indicated by their increasing courage to tell stories and answer simple questions. More significant progress was observed in the second cycle, where children were able to use simple sentences, tell stories with expression, and interact more actively with peers and teachers. It can be concluded that the use of hand puppet media can improve the speaking skills of children aged 4–5 years at TK Mutiara Insani. This medium is effective because it captures children’s attention, builds self-confidence, and provides an enjoyable learning experience